Peningkatan Hasil Belajar Mata Pelajaran Ekonomi Melalui Penerapan Strategi Pembelajaran Problem Based Learning Dan Pembelajaran Tugas Portofolio Mandiri Pada Siswa Kelas X IPS 1 SMA Muhammadiyah 1 SurakartaTahun Ajaran 2016/2017 - Hastuti, Ari Puji; , Dr.Suyatmini,SE.,M.Si (2017)
The purpose of this study is to improve student learning outcomes in the learning economy through learning strategies of Problem Based Learning and independent portfolio tasks in class X IPS-1 SMA Muhammadiyah 1 Surakarta. This type of research is the PTK (Classroom Action Research) by using a data analysis of student progress from the first cycle to the second cycle. The research subject of this class action is a class X IPS-1 SMA Muhammadiyah 1 Surakarta by the number of students 40 students. The subject of the implementation of the action is a researcher assisted by subject teachers of Economics. Classroom action research using data collection methods such as observation, interviews, and documentation. The procedures in this study there are four stages: planning, implementation, observation, and reflection. Data analysis technique used is critical for process analysis techniques and techniques for comparative results. The results of this study showed an increase in student learning outcomes in the learning economy through learning strategies and problem based learning portfolio tasks independently. It can be seen from: 1) the student's attention to the teacher's explanation, 2) critical thinking skills, writing and communication, 3) the ability of students to express opinions, 4) gives a brilliant idea, 5) doing exercises. Before the action, only 12 students learn completed, not completed after action 28 to 30 children studied thoroughly incomplete 10 so, can succeed in overcoming the low learning outcomes or a decline of 45%. Based on the description above can be concluded that the application of the method of problem based learning and independent portfolio tasks can improve student learning outcomes. Keywords: results studying economics, pbl strategies, and tasks portfolio mandiri